2011
DOI: 10.1021/nn200580w
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap Opening in Graphene Antidot Lattices: The Missing Half

Abstract: The electronic structure of graphene antidot lattices (GALs) with zigzag hole edges was studied with first-principles calculations. It was revealed that half of the possible GAL patterns were unintentionally missed in the usual construction models used in earlier studies. With the complete models, the bandgap of the GALs was sensitive to the width W of the wall between the neighboring holes. A nonzero bandgap was opened in hexagonal GALs with even W, while the bandgap remained closed in those with odd W. Simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
163
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(176 citation statements)
references
References 65 publications
13
163
0
Order By: Relevance
“…S9). These results open up another route for using graphene anti-dots to modify the electronic properties of graphene 25,26 . Why does the GNB emerge randomly on the surface?…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…S9). These results open up another route for using graphene anti-dots to modify the electronic properties of graphene 25,26 . Why does the GNB emerge randomly on the surface?…”
Section: Resultsmentioning
confidence: 83%
“…4) at 650 K ( < etching temperature reported). Regular array of these holes on graphene can form antidots lattice that have been predicted to generate spin qubits 25,26 .…”
Section: Resultsmentioning
confidence: 99%
“…Throughout in this paper we focus on triangular graphene antidot lattices: these systems are known to lead to a gap in the electronic spectrum, 42,43 which is essential for the present purposes. Due to the high lattice symmetry the number of independent lattice parameters is small, and furthermore, these systems are the most thoroughly studied, both theoretically and experimentally.…”
Section: Systems and Methodsmentioning
confidence: 99%
“…40 GALs have been proposed as a flexible platform for creating a semiconducting material with a band gap which can be tuned by varying the antidot size, shape, or lattice symmetry. 17,[41][42][43] GALs can be fabricated by electron beam lithography, 44,45 by block copolymer lithography 46,47 with hole distances down to 5 nm, and at a larger scale through nanorod photocatalysis 48 and anisotropic etching. 49 To the best of our knowledge, no studies have been reported on the thermal properties of finite GALs.…”
Section: Introductionmentioning
confidence: 99%
“…In GAL structure, the bandgap opening depends on the dimension of the holes as well as the wall distance between the holes. 17 The bandgap opening makes a nonzero effective mass which considerably degrades carrier mobility, resulting in an inverse relation with mobility in the graphene nanoribbon structures. 18 The electrical conductivity values in 3D-GN are higher than the previously reported values for nanoporous carbon 19 (3030 S/m).…”
Section: Thermoelectric Properties Of Nanoporous Three-dimensional Grmentioning
confidence: 99%